Frequency and Symptoms of Odontogenic Sinusitis: A Cross-Sectional Study - Jahandideh, Hesam; Ghadimi, Fargol; Behboudi, Edris; Omidvari, Ali (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2023)
Background: Occasionally, chronic sinusitis has a dental origin. This Entity is usually resistant to common treatments and high clinical suspicion is necessary for its diagnosis. The symptoms of odontogenic sinusitis are similar to the symptoms caused by other causes of sinusitis, and so far no special symptoms have been introduced for it. In this study, we decided to measure the frequency of this disease and its symptoms. Aim: The aim of this study was to examine people with dental sinusitis in CT scan (with or without clear signs of sinusitis) and also to examine the prevalence of sinonasal symptoms in all patients as well as the group with odontogenic sinusitis. Methods: All candidates for septorhinoplasty in 2018 who came to the otorhinolaryngology clinic of Firoozgar Hospital, Tehran, Iran were included in the study. The coronal CT scan of the maxillary sinus of these people were checked for odontogenic sinusitis and at the same time the SNOT-22 sinonasal symptoms questionnaire was completed by the patients. Finally, the prevalence of odontogenic sinusitis and sinonasal symptoms among these patients have been examined. Results: Twenty-eight of 100 patients had evidence of chronic sinusitis. The prevalence of odontogenic sinusitis in the studied population was 17%. The average score of SNOT-22 was 34.23 ± 8.87 in patients with chronic sinusitis and 38.0 ± 10.45 in patients with odontogenic sinusitis. Conclusion: Sinonasal symptoms in patients with odontogenic sinusitis had a low prevalence and no special symptom can be considered to differentiate this disease from other causes of sinusitis.